The Effect of Various Composite Resin Types, Surface Treatments, and Repaired Materials on the Shear Bond Strength of Composite Resin Repair - Diyar Kh Bakr (Erbil Dental Journal)
Background and Objectives: Composite resin are widely used in the field of restorative dentistry, as the time passes, composite resin restoration are subjected to failure. This in vitro study conducted to evaluate the effect of two types of composite resin, surface treatment, and three types of repaired materials on shear bond strength.